Super edge-magic labeling of accordion and bracelet graphs - Baig A.Q.; Afzal, Hafiz U.; Imran M.; Bashir M.S.; Qureshi R.J. (Utilitas Mathematica, 2017)
Let G = (V, E) be a finite, simple and undirected graph with vertex set V(G) and edge set E(G). Graph G is called edge-magic if there exists a bijective function f, f: V(G) ∪ E(G) 1,2,..., |V(G)| + |E(G)| such that f(u) + f(uv) + f(v) is a constant for each edge uv ϵ E(G). An edge-magic labeling f is called super edge-magic if the vertices are labeled with the smallest possible numbers. In this paper, we are dealing with the super edge-magic labeling of accordion and bracelet graphs.